Assessment of field performance and genetic diversity analysis of tissue culture variants of strawberry - Haque, S.; Nath, U. K.; Iqbal, S.; Khatun, R. A.; Jani, A. H. A. A. (International Journal of Agricultural Technology, 2015)
The present experiment was conducted to select suitable high yielded stable strawberry variants through micro propagation. Reproducible protocols for in vitro proliferation of plantlets through shoot tip and nodal segment explants had shown significant variation in callus induction as influenced by BAP 1.0 mg L-1. The concentration of BAP exhibited significant influence on the percentage of callus induction. The regenerated shoots were cultured on shoot induction media containing different combined concentrations of BAP and NAA 1.0 BAP and 0.5 mg L-1 and those were sub-cultured on MS medium supplemented with combination of BAP 1.5 mg L-1 and IBA 1.0 mg L-1 in order to allow root. Among the tissue culture variants of strawberry giving emphasis on key yield parameter e.g. petiole length, days to flowering, number of fruits plant-1, % brix and weight of individual fruit tissue culture variants G-9, G-10 and G-11 were selected as superior variants for cultivation across all the environments. Significant variation among the variants was found for all the characters. It was found that yield plant-1 was positively correlated with petiole length, days to opening of first flower, number of fruits plant-1, % brix and weight of individual fruit. Path analysis revealed that petiole length, crown spread plant-1, pollen sterility, no. of fruits plant-1, ascorbic acid content of individual fruit and weight of individual fruit had positive direct effects on fruit yield plant-1. The genotypes were grouped into three clusters based on Euclidean distance following Ward’s method and highest intra cluster distance was found in cluster III and inter cluster distance was observed between genotypes of cluster I and III.